Type-2 Fuzzy Logic Controller Based PSS for Large Scale Power Systems Stability - Kahouli, O.; Ashammari, B.; Sebaa, K.; Djebali, M.; Abdallah, H. H. (Engineering, Technology & Applied Science Research, 2018)
In this paper, the application of the fuzzy logic based power systems stabilizer (FLPSS) to damp power system oscillation is presented. Various types of fuzzy logic controller are used to replace the conventional power system stabilizer (CPSS). The classic fuzzy logic controller based PSS (FLCPSS), the polar FLC (PFLCPSS) and the interval type-2 fuzzy logic controller based PSS (IT2FLCPSS) are applied to the New England - New York interconnected power system and the obtained results are compared. For coordination purposes, genetic algorithm (GA) is used to tune the FLCPSS’s gains. The non-linear simulation in the presence of noise confirms the robustness and the superiority of the IT2FLCPSS.